Nicolás Rosa, The Youth of the Critic - Podlubne, Judith (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In the mid-1950’s, the young Nicolás Rosa contributed to Democracia, a newspaper from Rosario City. These collaborations, composed by notes and accounts, became the milestone of his initiation as a writer within cultural journalism. The purpose of the article is to portray the corpus of materials surveyed in the archive research, unknown to specialized readers, and to examine the critic’s image depicted in them from a biographical perspective, that is, incorporating the biographical process into the writing of the article. This perspective not only allows to replenish his initial self-figurations but also to conjecture around the circumstances that would have transformed him into a Barthesian critic